Role of adjuvant therapy in intermediate-risk cervical cancer patients - Subanalyses of the SCCAN study - Cibula, David; Akilli, Huseyin; Jarkovsky, Jiri; van Lonkhuijzen, Luc; Scambia, Giovanni; Meydanli, Mehmet Mutlu; Ortiz, David Isla; Falconer, Henrik; Abu-Rustum, Nadeem R; Odetto, Diego; Klát, Jaroslav; Dos Reis, Ricardo; et al. (Gynecologic oncology, 2023)
OBJECTIVE: The "intermediate-risk" (IR) group of early-stage cervical cancer patients is characterized by negative pelvic lymph nodes and a combination of tumor-related prognostic risk factors such as tumor size ≥2 cm, lymphovascular space invasion (LVSI), and deep stromal invasion. However, the role of adjuvant treatment in these patients remains controversial. We investigated whether adjuvant (chemo)radiation is associated with a survival benefit after radical surgery in patients with IR cervical cancer. METHODS: We analyzed data from patients with IR cervical cancer (tumor size 2-4 cm plus LVSI OR tumor size >4 cm; N0; no parametrial invasion; clear surgical margins) who underwent primary curative-intent surgery between 2007 and 2016 and were retrospectively registered in the international multicenter Surveillance in Cervical CANcer (SCCAN) study. RESULTS: Of 692 analyzed patients, 274 (39.6%) received no adjuvant treatment (AT-) and 418 (60.4%) received radiotherapy or chemoradiotherapy (AT+). The 5-year disease-free survival (83.2% and 80.3%; PDFS = 0.365) and overall survival (88.7% and 89.0%; POS = 0.281) were not significantly different between the AT- and AT+ groups, respectively. Adjuvant (chemo)radiotherapy was not associated with a survival benefit after adjusting for confounding factors by case-control propensity score matching or in subgroup analyses of patients with tumor size ≥4 cm and <4 cm. In univariable analysis, adjuvant (chemo)radiotherapy was not identified as a prognostic factor in any of the subgroups (full cohort: PDFS = 0.365; POS = 0.282). CONCLUSION: Among patients with IR early-stage cervical cancer, radical surgery alone achieved equal disease-free and overall survival rates to those achieved by combining radical surgery with adjuvant (chemo)radiotherapy.
Keywords: adjuvantní radioterapie; Radiotherapy; Retrospective Studies; Cervical cancer; Prognosis; GOG criteria; Hysterectomy; nádory děložního čípku; Radial surgery; Intermediate risk; kombinovaná terapie; Neoplasm Staging; ženské pohlaví; prognóza; retrospektivní studie; Humans; Adjuvant treatment; Combined Modality Therapy; staging nádorů; Uterine Cervical Neoplasms; hysterektomie; Female; Radiotherapy, Adjuvant; lidé